NR4A Receptors Differentially Regulate NF-κB Signaling in Myeloid Cells - McEvoy, Caitriona; de Gaetano, Monica; Giffney, Hugh E.; Bahar, Bojlul; Cummins, Eoin P.; Brennan, Eoin P.; Barry, Mary; Belton, Orina; Godson, Catherine G.; Murphy, Evelyn P.; Crean, Daniel (Frontiers in Immunology, 2017)
Dysregulation of inflammatory responses is a hallmark of multiple diseases such as atherosclerosis and rheumatoid arthritis. As constitutively active transcription factors NR4A nuclear receptors function to control the magnitude of inflammatory responses and in chronic inflammatory disease can be protective or pathogenic. Within this study we demonstrate TLR4 stimulation using the endotoxin lipopolysaccharide (LPS) rapidly enhances NR4A1-3 expression in human and murine, primary and immortalized myeloid cells with concomitant gene transcription and protein secretion of MIP-3α, a central chemokine implicated in numerous pathologies. Deficiency of NR4A2 and NR4A3 human and murine myeloid cells reveals both receptors function as positive regulators of enhanced MIP-3α expression. In contrast within the same cell types and conditions, altered NR4A activity leads to suppression of LPS induced MCP-1 gene and protein expression. An equivalent pattern of inflammatory gene regulation is replicated in TNFα treated myeloid cells. We show NF-κB is the critical regulator of NR4A1-3, MIP-3α and MCP-1 during TLR4 stimulation in myeloid cells and highlight a parallel mechanism whereby NR4A activity can repress or enhance NF-κB target gene expression simultaneously. Mechanistic insight reveals that NR4A2 does not require DNA binding capacity in order to enhance or repress NF-κB target gene expression simultaneously, and establishes a role for NF-κB family member Relb as a novel NR4A target gene involved in the positive regulation of MIP-3α. Thus, our data reveals a dynamic role for NR4A receptors concurrently enhancing and repressing NF-κB activity in myeloid cells leading to altered transcription of key inflammatory mediators